The Reality of Corruption and Its Combat in Arab Countries According to the Corruption Perceptions Index (2022–2024) - Chenini, Rachid (Future Science, 2025)
The present study aims to examine the reality of corruption and anti-corruption efforts in Arab countries based on the Corruption Perceptions Index (2022–2024). To achieve this, the research paper is structured into two main sections: the first section addresses Transparency International, while the second focuses on the Corruption Perceptions Index data for Arab countries during the period 2022–2024. The study concludes that Arab countries suffer from a flawed approach to combating corruption. These countries primarily adopt reactive rather than preventive strategies. Furthermore, they have failed to develop integrity systems, as well as effective anti-corruption policies and mechanisms. They also show a lack of seriousness in implementing and maintaining anti-corruption measures. In many cases, their governments face significant challenges due to pre-existing corrupt systems, which limit their ability to address the root causes of corruption.